Grammatical Error Analysis of English Abstracts Translation in Jurnal Ilmiah Ekonomi Islam (JIEI) Journal - Fitria, Tira Nur (Lite (Semarang, Indonesia), 2021)
Scientific writing like abstract demands perfect grammar writing in academic language. A common error usually is the use of an automated translator such as Google Translate to translate abstracts from Indonesian to English. The translation produced needs to be polished again to avoid mistakes in the grammar itself. The objective of this research is to find the type of grammatical error in English abstracts published in Jurnal Ilmiah Ekonomi Islam (JIEI) journal in 2020 both English and Indonesian. This research uses descriptive qualitative. The result of the study shows that three types of grammatical errors found in English abstracts in the JIEI journal are misinformation, omission, and addition. In misinformation error, there are 98 data or 44.5 %. In omission error, there are 69 data or 31.36 %. In addition to error, there are 53 data or 24.09 %. In misinformation, several errors were found in the use of part of speech such as article/determiner, the preposition, verb (subject-verb agreement), noun (singular-plural), and pronoun. In omission, several errors were found in the omission of part of speech such as article ‘a, an, the’, preposition ‘on’ and ‘to’. In addition, several errors were found in the addition part of speech such as article/determiner ‘a, an, the”, preposition “of, to, in, on, at”. Preposition sometimes is not used with certain verbs and expressions. The most dominant type of grammatical error is misinformation. There is the misuse of grammar forms into other grammatical forms in the use of part of speech such as in the determiner/article, preposition, verb, noun, and pronoun.